ANALISIS KETERAMPILAN DASAR MENGAJAR GURU BIDANG STUDI EKONOMI KELAS X DI SMA SWASTA WALISONGO PONTIANAK - Syahril, Syahril; Asriati, Nuraini; Parijo, Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTÂ This study aims to examine: (1) basic skills of teaching teachers in the field of economics class X at Walisongo Senior High School Pontianak (2) the dominant teaching skills of teachers dominantly used by teachers of economics class X at Private High School Walisongo Pontianak. This research is a qualitative research that describes the real situation as what should happen when the researchers do. The implementation of this research is conducted at SMA Swasta Walisongo Pontianak, starting from 20 until 30 November 2017. The research subjects are one teacher of economics class X at Private High School Walisongo Pontianak. Data collection techniques used are observation and documentation sheets. The results obtained in the study that: (1) Basic Questioning Skills got an average grade of 3.66 with category A, (2) Questioning Skills obtained an average score of 2.38 with category C, (3) Enabling Gaining Skills 3.88 with category A, (4) Variation Skill obtained an average score of 2.60 with category C, (5) Explaining Skills earned an average rating of 3.91 with category A, (6) Skills Opening And Closing Lessons obtained an average score of 3.33 with category B, (7) Numeracy Guiding Small Group Discussion got an average score of 2.50, (8) Skills of Classroom Management earned an average grade of 3.85 with category A. Overall assessment with the teacher appraisal tool (APKG) has 4 times the meeting obtained the average value of 3.20 with category B. Of the eight basic skills of teaching, the skills to explain the more dominant use by teachers of economics class X in the SMA Swas ta Walisongo.Â Keywords: Basic Teaching Skills, APKG, Field of Economic Studies